(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
This article presents data on the prevalence of various types of heart remodeling in patients with type 2 diabetes with DN. It was found that the severity of structural and functional changes in the heart depends on the stage of diabetic nephropathy. New data are presented that establish a clear relationship between the indicators characterizing the structural and functional state of the heart and kidneys in patients with type 2 diabetes with DN. New facts have been obtained indicating that the basis of combined renocardial disorders in patients with type 2 diabetes is impaired vascular endothelial function.